1998
DOI: 10.1006/viro.1998.9324
|View full text |Cite
|
Sign up to set email alerts
|

Psittacine Beak and Feather Disease Virus Nucleotide Sequence Analysis and Its Relationship to Porcine Circovirus, Plant Circoviruses, and Chicken Anaemia Virus

Abstract: Cloning and sequencing of the circular, single-stranded DNA of one isolate of psittacine beak and feather disease virus (BFDV) demonstrate a genome composed of a circular molecule of 1993 nucleotide bases. An analysis of the assembled replicative form demonstrated seven open reading frames (ORFs) (three in the virion strand and four in the complementary strand), potentially encoding seven viral proteins of >8.7 kDa. High amino acid sequence similarity was demonstrated between a potential 33.3-kDa protein produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0
6

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(101 citation statements)
references
References 37 publications
0
95
0
6
Order By: Relevance
“…CAV, PBFD virus and porcine circovirus. Yet recent DNA cloning and sequencing studies have described striking similarities between porcine circovirus and Pigeon circovirus infection 155 PBFD virus genomes (Niagro et al, 1998), whereas no such homologies were found when these two viruses were compared with CAV (Bassami et al, 1998). The pigeon circovirus has been described as antigenically distinct from PBFD virus, although possible homologous DNA sequences, as demonstrated by DNA in situ hybridization, have been found between both viruses (Woods et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CAV, PBFD virus and porcine circovirus. Yet recent DNA cloning and sequencing studies have described striking similarities between porcine circovirus and Pigeon circovirus infection 155 PBFD virus genomes (Niagro et al, 1998), whereas no such homologies were found when these two viruses were compared with CAV (Bassami et al, 1998). The pigeon circovirus has been described as antigenically distinct from PBFD virus, although possible homologous DNA sequences, as demonstrated by DNA in situ hybridization, have been found between both viruses (Woods et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Circoviruses are tiny non-enveloped icosahedral viruses (15-24 nm in diameter) with a single-stranded circular DNA of 1.76 kb to 2.31 kb (Bassami et al, 1998;Niagro et al, 1998). Like most other members of the newly proposed Circoviridae family, PiCV is characterized by typical basophilic globular inclusions in light microscopy (Woods et al, 1993;Shivaprasad et al, 1994;Woods et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Virus detection in live birds can be achieved by haemagglutination using erythrocytes from goffin cockatoos, guinea pigs or galahs (Ritchie et al, 1991;Raidal et al, 1993). The determination of the complete nucleotide sequence of BFDV was the basis for establishment of molecular detection methods, especially polymerase chain reaction (PCR) (Ritchie et al, 1989;Bassami et al, 1998Bassami et al, , 2001. Ypelaar et al (1999) tested several primer combinations that hybridized with various regions of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…It carries single-stranded circular DNA with a complete genome size of about 2 kb (2,18,32). PBFDV is a member of the genus Circovirus in the family Circoviridae (1,18).…”
mentioning
confidence: 99%